Behavioural interventions for smoking cessation: an overview and network meta-analysis - Hartmann-Boyce, J; Hartmann-Boyce, J; Livingstone-Banks, J; Livingstone-Banks, J; Ordonez-Mena, J; Ordonez-Mena, J; Theodoulou, A; Theodoulou, A; Fanshawe, T; Fanshawe, T; Aveyard, P; Aveyard, P; et al. (University of Oxford, 2020)
Supplementary tables in Microsoft Word and Excel that provide additional information to accompany the Cochrane Overview: Behavioural interventions for smoking cessation: an overview and network meta-analysis